Methane dynamics of a constructed fen in the Athabasca Oil Sands Region, Alberta - Murray, Kimberley (University of Waterloo, 2017)
Oil sands mining activities in the Athabasca Oil Sands Region in northeastern Alberta, Canada have resulted in an extensive amount of land disturbance. The Alberta government requires some reclamation of disturbed land to be to wetland ecosystems, and given the predominance of fen peatlands in the area, fen construction on post-mined landscapes has recently been attempted. Peatlands sequester substantial amounts of carbon over thousands of years due to waterlogged conditions and inefficient decomposition, and on a large time scale provide a cooling effect on the planet’s radiative budget. However, peatland conditions are also ideal for production of the strong greenhouse gas methane (CH4). Natural peatlands emit a significant amount of CH4 to the atmosphere, particularly following formation when these ecosystems have a net warming effect associated with the large CH4 flux. Given the knowledge that the conditions that are conducive to CH4 production and flux in natural peatlands also result in the eventual accumulation of peat and carbon sequestration, understanding the CH4 dynamics of constructed fens may indicate biogeochemical function, along with the ability of these ecosystems to ultimately accumulate peat, a major goal of reclamation. Further, understanding important controls on CH4 dynamics from the constructed fen, including vegetation and geochemistry, in comparison to natural sites, is beneficial for the development of recommendation that may result in lower CH4 flux through vegetation impacts, but appropriate water chemistry for peat accumulation. For this research CH4 flux, CH4 concentration, and variables including vegetation and hydrochemistry were monitored from a constructed fen and two natural reference sites in northeastern Alberta over the 2015 growing season. A factorial greenhouse experiment was also used to understand differences in CH4 flux, concentration, and oxidation between two vascular plants, Carex aquatilis and Juncus balticus, planted for fen construction. This greenhouse experiment ...